Complications of Radiofrequency Ablation for Hepatic Hemangioma: A Multicenter Retrospective Analysis on 291 Cases - Wu, Shilun; Gao, Ruize; Yin, Tao; Zhu, Ruhang; Guo, Shigang; Xin, Zonghai; Li, Aolei; Kong, Xinliang; Gao, Jun; Sun, Wenbing (Frontiers in Oncology, 2021)
Purpose To report the complications of radiofrequency ablation (RFA) for hepatic hemangioma. Patients and Methods Investigators from six centers performed RFA for hepatic hemangioma and used a standardized follow-up protocol. Data were collected from 291 patients, including 253 patients with hepatic hemangioma 5 to 9.9 cm in diameter (group A) and 38 with hepatic hemangioma ≥ 10 cm (group B). Technical success, complete ablation, and complications attributed to the RFA procedure were reported. Analysis of variance was used to determine whether the major complication rate was related to tumor size or clinical experience. Results A total of 304 lesions were treated in 291 patients. Technical success was achieved without adverse events in all cases. A total of 301 lesions were completely ablated, including 265 of 265 (100%) lesions in group A, and 36 of 39 (92.31%) in group B. The rate of technology-related complications was similar in groups A and B (5.14% (13/253) and 13.16% (5/38), respectively; P = 0.121). Moreover, all technology-related complications occurred during the early learning curve period. The rate of hemolysis-related complications in two groups were 83.40% (211/253) and 100% (38/38) (P =0.007) and the systemic inflammatory response syndrome-related complications in two groups were 33.99% (86/253) and 86.84% (33/38) (P<0.001). There were no delayed complications in either group. Conclusion RFA is minimally invasive, safe, and effective for hepatic hemangiomas 5 to 9.9 cm in diameter. More clinical data are needed to confirm the safety of RFA for hepatic hemangiomas ≥ 10 cm.